Uncovering Linguistic Anomalies: An Analysis of Language Errors in Internship Reports of Polsri Business Administration Students: - Luciana Lidya Sari; Eka Putri; Sri Wahyuni; Wasitoh Meirani (Raja Zulkarnain Education Foundation, 2025)
This research aims to identify the dominant forms of linguistic anomalies or language errors in internship reports written by Business Administration students at Politeknik Negeri Sriwijaya (Polsri), analyze their causative factors, and explore their implications for professional competence. The study employed a qualitative descriptive approach utilizing the Error Analysis (EA) framework based on the Indonesian General Guidelines for Spelling (PUEBI) and standard Indonesian grammar. The sample consisted of 30 internship reports from 2024 Business Administration students selected through purposive sampling.Analysis of a total of 880 linguistic anomalies (estimated) revealed that Spelling and Punctuation (SP) errors ranked the highest, accounting for 37.50% of the total errors. The most frequent sub-category within this domain was Standard Word Usage (15.34%) (e.g., Praktek instead of Praktik). The second highest was Morphological and Syntactical (MS) errors (34.66%), with Ineffective Sentences (24.43%) being the primary syntactical issue (characterized by word redundancy and the use of non-standard conjunctions like Dimana). These errors are attributed to a combination of intralingual factors (overgeneralization of affixation rules) and extralingual factors (interference from spoken/informal register). Overall, these findings have serious implications, namely diminishing the reports’ credibility and fostering a negative perception of students’ professionalism within the industry due as they are perceived as careless and lacking meticulousness.